Growth factor-dependent and independent regulation of skeletal muscle mass - Is IGF-1 necessary for skeletal muscle hypertrophy? - - Mitsunori Miyazaki (Japanese Society of Physical Fitness and Sports Medicine, 2013)
Pituitary growth hormone (GH) and insulin-like growth factor-1 (IGF-1) play a critical role in the regulation of postnatal organ growth and overall body size. IGF-1 has been indicated as a very effective anabolic agent, and thus considered a critical regulator of skeletal muscle hypertrophy in response to increased workload such as resistance exercise. In contrast, recent studies using a genetic model of IGF-1/IGF-1 receptor have indicated that functional IGF-1-dependent mechanisms are not an absolute requirement for growth/hypertrophy in mature skeletal muscle. In this brief review, classic and recent aspects in hormonal/growth factor-dependent regulation of skeletal muscle mass are discussed. This review will particularly focus on 1) functional requirements of IGF-1 regulation in skeletal muscle hypertrophy and 2) cellular mechanisms in the regulation of protein synthesis in skeletal muscle.